Soil acidification controls invasive plant species in the restoration of degraded Cerrado grasslands - Lira‐Martins, Demétrius; Xavier, Rafael O.; Mazzochini, Guilherme G.; Verona, Larissa S.; Andreuccetti, Thalia; Martins, Éder S.; Barros, Fernanda V.; Furtado, Mariana N.; Stein, Bethina; Abrahão, Anna; Sampaio, Alexandre; Schmidt, Isabel; et al. (Restoration ecology, 2025)
The Cerrado, South America's largest savanna, has acidic, nutrient‐poor soils and its native plants thrive under these conditions. However, abandoned pastures historically undergo changes in chemical properties due to interventions like liming and fertilizer use. This favors invasive African grasses and hinders native plants, impacting restoration efforts. In a Cerrado grassland undergoing restoration study, we tested whether soil acidification could restore native soil conditions and control invasives using 56 plots across 14 blocks. We hypothesized that decreased soil pH and nutrient availability would reduce invasive biomass and enhance diversity. We show that acidification reduced invasive biomass by 71%, with acidification negatively affecting invasives while sparing natives. Maintaining nutrient‐poor soil conditions can help to control invasive grasses in restoration projects, as fertilizer application can favor invasive species establishment. Soil acidification effectiveness depends on local nutrient levels. Areas with high soil cation content may require larger amendment quantities. Restoration strategies in nutrient‐poor ecosystems should aim recovering historical soil conditions to control invasives growth and support slow‐growing native plants.